2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6944269
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary investigation of effects of a quasi-passive knee exoskeleton on gait energetics

Abstract: In this paper, we explain that the human knee behavior in the weight acceptance phase of gait (first ~40% of gait cycle) resembles that of a linear torsional spring. This led us to study the effects of the assistance provided by a pair of quasi-passive knee exoskeletons, which implement springs in parallel with the knee joints in the weight acceptance phase. Using the exoskeletons in a series of experiments on seven participants, we found that the exoskeleton mildly but non-significantly reduces the metabolic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The kinematic constraints imposed by the exoskeleton joint resulted in a slightly more flexed knee at the heel strike, which could be a result of limited range of motion of the exoskeleton joints (as fabrication imperfection), as it was reported by the participants about the left exoskeleton. In another study, we found that the exoskeleton mass is the main contributor to the increase in the metabolic cost of walking [59]. Here we found that the exoskeleton mass caused an upscale in the range of joint moments suggesting that minimization of the exoskeleton mass should be a main goal in the design of exoskeletons.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…The kinematic constraints imposed by the exoskeleton joint resulted in a slightly more flexed knee at the heel strike, which could be a result of limited range of motion of the exoskeleton joints (as fabrication imperfection), as it was reported by the participants about the left exoskeleton. In another study, we found that the exoskeleton mass is the main contributor to the increase in the metabolic cost of walking [59]. Here we found that the exoskeleton mass caused an upscale in the range of joint moments suggesting that minimization of the exoskeleton mass should be a main goal in the design of exoskeletons.…”
Section: Discussionmentioning
confidence: 51%
“…ankle and hip) under the effect of assistance to the knee joint to examine the locality of the external stiffness effects. Lastly, we intend to investigate the effect of the exoskeleton on the metabolic cost of locomotion [59].…”
Section: Discussionmentioning
confidence: 99%
“…#W911NF-07-D-0001). Yale University Kamran Shamaei et al [131] studied the auxiliary effect provided by a quasi-passive knee exoskeleton (Figure 8f). The knee exoskeleton is composed of motors, worm gear sets, and springs assembled on the thigh segment of the exoskeleton.…”
Section: Knee-assisted Exoskeletonmentioning
confidence: 99%
“…This paper presents a brace concept that aims to reduce the first peak total KCF during gait through muscle compensation by applying an external knee extension moment. The concept of applying a knee flexion/extension moment to assist human muscles is common within exoskeletons, which either apply the moment actively [27][28][29][30] or quasi-passively [31][32][33][34]. The latter refers to an active control, but the moment is applied passively from, e.g., springs and, hence, there is no mechanical energy added to the system.…”
Section: Introductionmentioning
confidence: 99%
“…The main goal of exoskeletons is to provide assistance and compensate for the joint moments to reduce muscle activation, but the purpose can vary. When dealing with the lower extremity, metabolic cost is most often the main evaluation factor [31,35,36,40], which improves endurance for various activities and load-carrying tasks. However, as previously mentioned, the muscle compensation in the sagittal plane may also lead to a reduced KCF and thereby potentially slow down KOA progression.…”
Section: Introductionmentioning
confidence: 99%